Characterization of the complete chloroplast genome of Lycium barbarum (Solanales: Solanaceae), a unique economic plant to China. Issue 2 (3rd July 2018) - Jia, Guolun; Xin, Guiliang; Ren, Xiaolong; Du, Xiaomin; Liu, Huidong; Hao, Nan; Wang, Cuiping; Ni, Xilu; Liu, Wenzhe
Abstract: Lycium barbarum (Solanaceae) is a unique economic plant to China. The complete chloroplast (cp)genome was sequenced and assembled by using Illumina paired-end reads data. The circular cp genome is 155, 656 bp in size, including a pair of inverted repeat (IR) regions of 25, 451 bp, a large single copy (LSC) region of 86, 554 bp and a small single copy (SSC) region of 18, 200 bp. Besides, 15 genes possess a single intron, while another three genes (clpP, rps12 and ycf3) have a couple of introns. The GC content of entire L. barbarum cp genome, LSC, SSC and IR regions are 37.8%, 35.9%, 32.3%, and 43.2%, respectively. Phylogenetic analysis based on the concatenated coding sequences of cp PCGs showed that L. barbarum and Atropa belladonna are closely related with each other within the family Solanaceae.